2003
DOI: 10.1103/physrevb.68.054509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pinning on the vortex-lattice melting line in type-II superconductors

Abstract: The vortex-lattice melting line in three-dimensional type-II superconductors with pinning is derived by equating the free energies of the vortex system in the solid and liquid phases. We account for the elastic and pinning energies and the entropy change that originates from the disappearance of the phonon shear modes in the liquid. The pinning is assumed to be caused by point defects and to be not too strong so that the melting line lies inside the so-called bundle-pinning region. We show that the derived equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 45 publications
(102 reference statements)
3
45
0
Order By: Relevance
“…While the IRL does correspond to the appearance of flux pinning and a bulk critical current when cooling the sample, a quantitative description of the T irr ͑B͒ dependence requires detailed knowledge of the flux-pinning mechanism and the summation of the elementary pinning forces acting on the vortex lattice. However, at fields exceeding the field-dependent Ginzburg criterion, B Ͼ 1 3 T͑‫ץ‬B c2 / ‫ץ‬T͒Gi͑T / T c ͒ϳ 1 3 B c2 ͑T͒, and in the presence of only pointlike disorder, 22,23 it can be shown that all thermodynamic and transport properties should in principle depend only on the parameter…”
Section: Irreversibility Line and Upper Critical Fieldmentioning
confidence: 98%
“…While the IRL does correspond to the appearance of flux pinning and a bulk critical current when cooling the sample, a quantitative description of the T irr ͑B͒ dependence requires detailed knowledge of the flux-pinning mechanism and the summation of the elementary pinning forces acting on the vortex lattice. However, at fields exceeding the field-dependent Ginzburg criterion, B Ͼ 1 3 T͑‫ץ‬B c2 / ‫ץ‬T͒Gi͑T / T c ͒ϳ 1 3 B c2 ͑T͒, and in the presence of only pointlike disorder, 22,23 it can be shown that all thermodynamic and transport properties should in principle depend only on the parameter…”
Section: Irreversibility Line and Upper Critical Fieldmentioning
confidence: 98%
“…The small thermal energy in low-T c superconductors makes pinning of the vortex lattice much more significant 4 , hence phase transitions related to this pinning become an alternative theoretical scenario 5,6 . For example, a disordering transition in the vortex lattice of niobium has been observed 7 directly by small angle neutron scattering (SANS) and is associated with the peak effect 8 (increased pinning of the vortices, linked to a softening of the vortex lattice below T c2 (H )).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The precise nature of this transition and, more generally, the mechanism underlying vortex lattice melting is still under debate. Typical melting theories are based on variants of the Lindemann criterion with disorder, 29 or involve dislocation proliferation mechanisms. 30 The properties of dislocations in the vortex lattice have been the object of extensive theoretical investigations, [31][32][33][34] but grain boundaries are less studied although they are often observed in numerical simulations.…”
Section: Introductionmentioning
confidence: 99%